2018
DOI: 10.1371/journal.pone.0190897
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid gene faah2a modulates stress-associated behavior in zebrafish

Abstract: The ability to orchestrate appropriate physiological and behavioral responses to stress is important for survival, and is often dysfunctional in neuropsychiatric disorders that account for leading causes of global disability burden. Numerous studies have shown that the endocannabinoid neurotransmitter system is able to regulate stress responses and could serve as a therapeutic target for the management of these disorders. We used quantitative reverse transcriptase-polymerase chain reactions to show that genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Some of these findings have been replicated in animal models, yet it needs to be investigated what the neuronal changes observed in vitro mean in the context of adaptive SR. Our assay system and what we are learning from modeling stress in zebrafish will be a useful platform to screen for such neural pathways and molecular components. In fact, we have identified several genetic loci that alter the rapid locomotor response to salt challenge including novel genes discovered in a pilot screen of random insertional mutants and targeted knockouts of cannabinoid receptor 1 ( cnr1 ) or fatty acid amide hydrolase 2a ( faah2a ) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of these findings have been replicated in animal models, yet it needs to be investigated what the neuronal changes observed in vitro mean in the context of adaptive SR. Our assay system and what we are learning from modeling stress in zebrafish will be a useful platform to screen for such neural pathways and molecular components. In fact, we have identified several genetic loci that alter the rapid locomotor response to salt challenge including novel genes discovered in a pilot screen of random insertional mutants and targeted knockouts of cannabinoid receptor 1 ( cnr1 ) or fatty acid amide hydrolase 2a ( faah2a ) …”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish, a freshwater teleost, depend primarily on cortisol signaling for osmoregulation . We previously reported that WT larval zebrafish (4 dpf) display increased frequencies of locomotion (number of movement/min) in response to hyperosmotic stress and that knockouts of endocannabinoid signaling genes cnr1 and faah2a and several novel genetic loci discovered in a pilot forward genetic screen show altered locomotor response to hyperosmotic stress . Others have observed that larval zebrafish swim away from an area with an increased osmolarity …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the evolutionary standpoint, it is likely that the motivation and reward aspects of the central eCB/CB1R system co-evolved with the energy homeostatic aspect in order to coordinate feelings of pleasure with the successful acquisition of nourishment. As the search and pursuit of energy would have also entailed significant exposure to threats and stressors, the central eCB/CB1R system of zebrafish also influences the stress response and habituation to various stressors (124). In mammalian organisms, the eCBs of the pre-frontal cortex play a significant role in coping, resiliency, and termination of stress-activated glucocorticoid release induced by the hypothalamic-pituitary-adrenal (HPA) axis (125, 126).…”
Section: Metabolic Therapeutics Viewed Through Ecb/cb1r System Evolutionmentioning
confidence: 99%